Polyclonal and monoclonal antibodies against dihydrogriesenin, atrazine and Haemophilus paragallinarum, and their use in enzyme linked immunosorbent assays - Visser, Leon (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 1988.